Eksistensi Grup Musik Tegalan Joend Pro Di Slawi Kabupaten Tegal - Pratama, Narendra Yudha; Wafa, Mochammad Usman (Universitas Negeri Semarang, 2020)
Tegalan music is typical music of Tegal regency which lyrics use Ngapak language. A piece of music group that still exists until now is Joend Pro. Joend Pro's musical group was formed in the year 2009 by Imam Joend. Joend Pro's musical group is on the basis of the consciousness of Imam Joend, about the importance of the existence of the art area of the music as a characteristic of the regional arts of Tegal Regency. This research aims to know, describe, and analyze the existence of the Tegalan Pro music Group in Slawi Tegal Regency. This research uses qualitative descriptive methods with data collection through observations, interviews, documentation and library studies. The result of the study was to demonstrate the existence of the Joend Pro band. Joend Pro often conducts self-performing, provit performances, as well as entertainment invitations at government events. Joend Pro's musical group's existence is still acknowledged to exist until now by society. This is evidenced by the community's performance offerings to fill entertainment at weddings and other events.